Experimental Investigation on Effects of Central Air Jet on the Bluff-body Stabilized Premixed Methane-air Flame. (February 2017) - Tong, Yiheng; Li, Mao; Thern, Marcus; Klingmann, Jens; Weng, Wubin; Chen, Shuang; Li, Zhongshan
Abstract: Flame stabilized by a bluff-body is a common scene in many engineering applications due to the enhanced mixing characteristics, improved flame stability, and ease of combustion control. We recently designed a burner which has a conical bluff body with a central air injector. In the current work, effects of the central air jet on the heat load of the bluff body, the flame structures and the flame blowoff limits were investigated. It was found that the central air jet can significantly reduce the heat load to the bluff body. It is a considerable solution to the problem caused by the high heat load in practical applications. The flame structures and blowout limits were altered with the addition of central air jet as well. Different blowout behaviors caused by the air jet were observed and reported. The bluff-body could be cooled down by the center air injection but then it seems not to stabilize the flame any more.